Gender diversity and firm value: Evidence from UK financial institutions - Peter Agyemang-Mintah; Hannu Schadewitz (Emerald, 2022)
Purpose: The purpose of this research is first, to empirically examine if the appointment of females (Board Gender Diversity) onto the corporate boards of UK financial institutions can improve the firm’s value. The second purpose is to examine if having females on the boards of UK financial institutions can impact the firm’s value during the pre/post global financial crisis situation.
Design/methodology/approach: The paper uses secondary data obtained from DataStream covering 63 financial institutions over a period of 12 years. A number of additional statistical estimations, including Random Effects and Fixed Effects, are conducted in order to test the robustness of the findings.
Findings: The outcome of this empirical research shows that the presence of females on the corporate boards of UK financial institutions has a positive and statistically significant relationship to the firm’s value. Before the financial crisis era, that is, during the pre-crisis situation (2000-2006), our evidence reveals a positive and statistically significant impact on the firm’s value. This means that women contributed significantly to the firm’s value. However, after the financial crisis period, the presence of females on the board did not make any significant effect on the firm’s value. A reasonable explanation may be that, even though the financial crisis was over from 2009 to 2011, the entire UK economy was still experiencing an economic downturn and financial firms were no exception, irrespective of whether there was female representation on any corporate board. Overall, the findings are consistent with prior studies.
Originality/value: In spite of several research projects on board gender diversity (BGD), this research is unique when compared to other previous empirical works because, primarily, it will be the first time that such research will empirically ascertain board gender diversity and firm value in UK financial institutions and also during the pre/post financial crisis era. This paper contributes to the corporate governance literature by offering new insights on board diversity and firm’s value relationship. Overall, the results will help to fill any missing gaps on gender diversity and firm’s value in UK financial institutions.
Keywords: Gender diversity, firm’s value, UK, financial institutions, financial crisis
Paper type: Research paper